Axial behavior of square and circular concrete columns confined with CFRP sheets under elevated temperatures: Comparison with welded-wire mesh steel confinement. (November 2022) - Abadel, Aref A.; Masmoudi, Radhouane; Iqbal Khan, M.
Abstract: The main goal of this study was to carry out an experimental investigation of the effectiveness and the efficiency of using carbon fiber-reinforced polymer (CFRP) strips and welded wire mesh jackets for retrofitting square and circular columns exposed to highly elevated temperatures. The investigated variables included the geometry of the column, strengthening scheme, and heating temperature. The samples were divided into three groups. The first group contains column samples not exposed to elevated temperatures and had no strengthening applied. The second category contains un-strengthened column samples subjected to elevated temperatures; the third category comprises strengthened column samples exposed to elevated temperatures. The elevated temperature exposure consisted of heating the specimens to 600 °C for 3 h. The column samples were subjected to axial compression testing till failure. The test results showed that both the circular and square columns exhibited reductions in axial capacity and initial stiffness when exposed to elevated temperatures. The use of welded wire mesh confinement around the circular and square columns exposed to elevated temperatures provided a more significant increase in strength as well as stiffness compared to strengthening the columns with unidirectional CFRP strips. In contrast, the CFRP repaired heated columns exhibited a significant increase in ductility and deformation capability without any reduction in strength than the WWM jacketed heated columns. Furthermore, the confinement effectiveness of CFRP jacketing provides considerable confinement to micro-cracked concrete compared to the WWM jacketed RC circular columns. However, in square columns the confining effectiveness for WWM was better compared to CFRP strips. Moreover, the use of CFRP strips were ineffective for recovering the stiffness of columns exposed to elevated temperatures. In addition, the results demonstrated that the use of welded wire mesh confinement and CFRP strips are cost-effective retrofitting techniques that could be used for circular and square RC columns.